The Effectiveness of Cassava Leaf (Manihot esculenta C.) Flavonoid Quercetin as Dengue Virus-1 Antivirus in Vitro - Husnaya Rayasari; Dadan Ramadhan Apriyanto; Rama Samara Brajawikalpa; Beti Ernawati Dewi (GHMJ (Global Health Management Journal))
Background:  Dengue fever is a mosquito-borne disease that can cause severe symptoms and death, placing high burden on healthcare systems in tropical regions. Currently, there are no antiviral treatments. It has been proven that synthetic quercetin able to improve body performance and reduce the risk of infection as well as inhibit DENV replication. Cassava leaves (Manihot esculenta C.) contain anthocyanins (flavonoids) such as quercetin and it shows potential as antiviral agent as the synthetic as well.